CONTRIBUTION OF DEEP ELECTRICAL RESISTIVITY TOMOGRAPHY TECHNIQUE TO HYDROGEOLOGICAL STUDIES: CASES FROM AREAS IN KAVALA (NORTH GREECE) - Vargemezis, G.; Tsourlos, P.; Mertzanides, I. (Bulletin of the Geological Society of Greece, 2010)
The most common geophysical method widely used in hydrogeological surveys concerning deep investigations (150-300m of depth) is the resistivity method and particularly the Vertical Electric Sounding (VES) using the Schlumberger array. VES interpretations assume 1D geoelectrical structure yet it is obvious that such an interpretation assumption is not valid in many cases where 2D and 3D geological features exist. In such cases the application of geoelectrical techniques which can provide both vertical and lateral information concerning the resistivity variations is required. Techniques such as the electrical resistivity tomography, mostly used for the 2D and 3D geoelectrical mapping of near surface applications can be adapted to be used for larger investigation depths provided that modified equipment (viz. cables) is used. In the present paper, the application of deep electrical resistivity tomography (ERT) techniques is applied. ERT array of 21 electrodes, at a distance of 50 meters between them (total length 1000 meters) has been used in several studied areas located in the prefecture of Kavala (North Greece). In several cases near surface structure has been compared with VLF data. The aim of the survey was to study in detail the geological-hydrogeological structure the area of interest in order to suggest the best location for the construction of hydrowells with the most promising results. The 2D images of the geological structure down to the depth of at least 200 meters allowed the better understanding of the behaviour of layered geological formations, since in several cases resistivity values have been calibrated with data from pre-existing boreholes.